Growth and genome-based insights of Fe(III) reduction of the high-temperature and NaCl-tolerant Shewanella xiamenensis from Changqing oilfield of China - Yang, Jiani; Zhao, Dan; Liu, Tao; Zhang, Shuang; Wang, Weidong; Yan, Lei; Gu, Ji-Dong (Frontiers in Microbiology, 2022)
Introduction A facultative anaerobe bacterium Shewanella xiamenensis CQ-Y1 was isolated from the wastewater of Changqing oilfield in Shaanxi Province of China. Shewanella is the important dissimilatory metal-reducing bacteria. It exhibited a well potential application in biodegradation and bioremediation. Methods Genome sequencing, assembling and functional annotation were conducted to explore the genome information of CQ-Y1. The effect of temperatures and NaCl concentrations on the CQ-Y1 growth and Fe(III) reduction were investigated by UV visible spectrophotometry, SEM and XRD. Results Genomic analysis revealed its complete genome was a circular chromosome of 4,710,887 bp with a GC content of 46.50% and 4,110 CDSs genes, 86 tRNAs and 26 rRNAs. It contains genes encoding for Na+/H+ antiporter, K+/Cl− transporter, heat shock protein associated with NaCl and high-temperature resistance. The presence of genes related to flavin, Cytochrome c, siderophore, and other related proteins supported Fe(III) reduction. In addition, CQ-Y1 could survive at 10% NaCl (w/v) and 45°C, and temperature showed more pronounced effects than NaCl concentration on the bacterial growth. The maximum Fe(III) reduction ratio of CQ-Y1 reached 70.1% at 30°C without NaCl, and the reduction reaction remained active at 40°C with 3% NaCl (w/v). NaCl concentration was more effective than temperature on microbial Fe(III) reduction. And the reduction products under high temperature and high NaCl conditions were characterized as Fe3(PO4)2, FeCl2 and Fe(OH)2. Discussion Accordingly, a Fe(III) reduction mechanism of CQ-Y1 mediated by Cytochrome c and flavin was hypothesised. These findings could provide information for a better understanding of the origin and evolution of genomic and metabolic diversity of S. xiamenensis.